2019
DOI: 10.11604/pamj.2019.32.150.15764
|View full text |Cite
|
Sign up to set email alerts
|

Measles outbreak investigation in an urban slum of Kaduna Metropolis, Kaduna State, Nigeria, March 2015

Abstract: Introduction Despite availability of an effective vaccine, the measles epidemic continue to occur in Nigeria. In February 2015, we investigated a suspected measles outbreak in an urban slum in Rigasa, Kaduna State, Nigeria. The study was to confirm the outbreak, determine the risk factors and implement appropriate control measures. Methods We identified cases through active search and health record review. We conducted an unmatched case-control (1:1) study involving 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Our study finding is similar with the study conducted in Ethiopia, Nigeria, and Zimbabwe where the number of unvaccinated increased by 5, 14, and 3 times, respectively. 24 , 36 , 37 Low average coverage of MCV1 in the last four consecutive years in the district might have contributed to this. As low coverage increases susceptibility to measles infection, high coverage with two doses of the measles vaccine ensures herd immunity and decreases the spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study finding is similar with the study conducted in Ethiopia, Nigeria, and Zimbabwe where the number of unvaccinated increased by 5, 14, and 3 times, respectively. 24 , 36 , 37 Low average coverage of MCV1 in the last four consecutive years in the district might have contributed to this. As low coverage increases susceptibility to measles infection, high coverage with two doses of the measles vaccine ensures herd immunity and decreases the spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Our finding is line with an investigation conducted in Nigeria, where being unvaccinated increases by 14 times the risk of measles infection. 46 Conversely, different literature showed that homogeneous high vaccination coverage with two doses of measles vaccine is the cornerstone required for ensuring and sustaining high population immunity against measles. 1 , 4 , 28…”
Section: Discussionmentioning
confidence: 99%